Reclaiming narratives, histories, and feminisms - Ellappa, Shana Danielle (Rhodes University, 2026)
This dissertation investigates how three contemporary South African women artists of Indian heritage, Usha Seejarim, Ravelle Pillay and Alka Dass, deploy their artistic practices as intersectional feminist interventions to recover silenced histories and reimagine dominant narratives of race, gender and cultural identity in post-apartheid South Africa. The scope of this study is intentionally narrowed to focus exclusively on women artists of Indian heritage working in South Africa after 1994, thus largely excluding male artists, artists of other identities and heritages, and works created prior to the country's democratic transition. By explicitly setting these analytical boundaries, the research clarifies its commitment to investigating a specific demographic and historical moment, allowing for greater depth and clarity. Grounded in postcolonial theory, African feminisms, and Kimberlé Crenshaw’s framework of intersectionality, the study combines visual, thematic, contextual, and intersectional analyses with an autoethnographic methodology that positions the researcher as both an insider and a critical interlocutor. For example, Crenshaw’s concept of intersectionality vividly comes to life in Seejarim’s Squeeze, where scores of clothes pegs cluster together yet pull in different directions, visually evoking the simultaneous and intersecting pressures of gendered domestic work and racialised histories. In this way, the theory does not remain abstract, but immediately engages with the very motifs and materials at the heart of the artists' production. Chapter 1 reviews literature on autobiography, autoethnography, and the politics of representation to establish the study’s conceptual framework. Chapter 2 traces the sociohistorical trajectory of South African Indian communities, from nineteenth-century indenture through apartheid segregation to ongoing marginalisation, demonstrating how these layered injustices inform the artists’ embodied experiences. Chapter 3 presents detailed case studies: Seejarim’s reconfigured domestic objects that critique gendered labour; Pillay’s figurative canvases that explore displacement and resilience; and Dass’s mixed media assemblages that integrate personal narrative into collective memory. The analysis demonstrates that these artistic practices enact resistance, reclamation, and healing, challenge archival absences, and expand the canon of South African art history. (Cowan, 2024) By foregrounding the creative strategies of women situated at the intersections of race, gender, and diaspora, this dissertation addresses a significant gap in scholarship on post-apartheid visual culture and offers a nuanced model for curatorial and academic engagement with marginalised artistic voices (Pillay, n.d.).
artworks by South African women of Indian heritage
Keywords: Art, South African (http://id.loc.gov/authorities/subjects/sh85007905); Postcolonialism and the arts (http://id.loc.gov/authorities/subjects/sh2001001629); East Indian diaspora in art (http://id.loc.gov/authorities/subjects/sh2010012147); Narrative inquiry (Research method) (http://id.loc.gov/authorities/subjects/sh2006004688); Women artists (http://id.loc.gov/authorities/subjects/sh85147447); Art History; Indian South Africans (https://www.wikidata.org/wiki/Q4120990); Cultural memory (https://www.wikidata.org/wiki/Q574613); Autoethnography (https://www.wikidata.org/wiki/Q4826265)